Age-Related Decline in the Variation of Dynamic Functional Connectivity: A Resting State Analysis - Chen, Yuanyuan; Wang, Weiwei; Zhao, Xin; Sha, Miao; Liu, Ya’nan; Zhang, Xiong; Ma, Jianguo; Ni, Hongyan; Ming, Dong (Frontiers in Aging Neuroscience, 2017)
Normal aging was characterized by abnormal resting-state functional connectivity, including decreasing within network and increasing between networks with a stationary assumption of the functional connectivity over the scan time. Actually, the resting-state functional connectivity is manifested as time-varying over even minutes in recent years, showing great potential in the intrinsic interaction and organization of the brain. We assumed that dynamic functional connectivity was an intrinsic dynamic balance in resting brain and was altered with age increasing in this paper. Two groups of people (N=36 and ages 20-25 for young group; N=32 and ages 60-85 for old group) were employed from the public data sample of Nathan Kline Institute. Within group, we verified the reliability of dynamic functional connectivity with randomized phase method and investigated the connectivity variation pattern among networks. Between groups, we calculated and compared the difference of functional connectivity variation and the low frequency energy ratio of the functional connectivity fluctuation. Results indicated that the dynamic functional connectivity in aging brain happened with reduced variation and slowing fluctuation between networks. These results highly supported the basis of abnormity and compensatory in aging brain, and might provide a new insight into the aging mechanism.